1970
DOI: 10.1080/18811248.1970.9734650
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Chemical Studies with Cyclotron Beams, (I)

Abstract: Systematic studies on the LET effect in the radiolysis of organic liquids have been initiated using various types of heavy ions accelerated by cyclotron. First, the effects of differences in irradiation conditions, in particular beam current, stirring speed and concentration of solutes have been examined. Aerated aqueous ferrous sulfate solutions (Fricke solutions) were subjected to irradiation by protons and He ions of various energies, to take advantage of the well-established reaction mechanism of the syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
2
4
1
Order By: Relevance
“…Moreover, the curve slope varies with the α beam intensity set down in the irradiation cell. These results are consistent with the literature data which take into account the intensity in the G(Fe 3+ ) determination [6]. These authors have shown that higher is the intensity higher is the G(Fe 3+ ) value.…”
Section: In Situ Fricke Dosimetrysupporting
confidence: 83%
See 4 more Smart Citations
“…Moreover, the curve slope varies with the α beam intensity set down in the irradiation cell. These results are consistent with the literature data which take into account the intensity in the G(Fe 3+ ) determination [6]. These authors have shown that higher is the intensity higher is the G(Fe 3+ ) value.…”
Section: In Situ Fricke Dosimetrysupporting
confidence: 83%
“…It thus assumes that, under our experimental conditions, the use of a Faraday cup is quite satisfactory. The dependence of G(Fe 3+ ) with the energy of the α particles was already observed in the literature [6,8]. This dependence can be explained qualitatively by track theory.…”
Section: Ex Situ Fricke Dosimetrysupporting
confidence: 62%
See 3 more Smart Citations